Serious games with recommendation techniques for obesity awareness / Muhammad Syafiq Mohd Omar - Mohd Omar, Muhammad Syafiq (2019)
Serious games is a games that have ability to motivate behavior in serious context, in which can change the attitudes, behaviors and habits of players. To create obesity awareness, the existing serious games are available but they are lacking of information, in which not taking an account of importance in giving the feedback or knowledge during gameplay, that can change behavior or habit of obese people. The authors investigate situation awareness model and behavioral change model in understanding the process in achieving awareness. Besides, the authors also exploring an important serious game elements in term of storyline, gameplay, interface and visualization that can help players in achieving their awareness. The authors also investigate recommendation technique which includes content-based filtering techniques, collaborative filtering technique and hybrid filtering technique to be implemented in serious games in order to raise obesity awareness. In addition, the development and testing of the games are also been explained. Both results from control group testing and experimental group testing are discussed and compared.